Factors Determining Investor Acceptance Towards Islamic Finance in India - Irfan, Mohammad; Chowdhury, Shah Saeed Hassan; Rusmita, Sylva Alif (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2021)
Despite India, having the second largest Muslim population in the world, Islamic finance is in its nascent stage. Thus, it is important from the perspective of the investor to understand the concept of Islamic Finance. This study scrutinizes the factors affecting the acceptance of Islamic Finance in India. A questionnaire was distributed to collect data from 354 investors from cities across India with snowball sampling. The results of the study reveal the high degree of reliability and validity of the data as reflected by Cronbach’s Alfa (α) at 0.86. Kaiser-Mayer-Olkin Measure of Sampling Adequacy (KMO) is .776, which is statistically significant. Factor analysis extracted highly loaded (Eigen value > 1) consisting of six factors with 29 items. Together these six factors explained a total variance of 76.24%. These factors are Awareness of Shariah indices, Religious motive, Social responsiveness, Understanding of Shariah screening, Ethical investment, and Socio-economic reasons.